2013
DOI: 10.1371/journal.pone.0082955
|View full text |Cite
|
Sign up to set email alerts
|

Conversion of Exogenous Cholesterol into Glycoalkaloids in Potato Shoots, Using Two Methods for Sterol Solubilisation

Abstract: Steroidal glycoalkaloids (SGA) are toxic secondary metabolites naturally occurring in the potato, as well as in certain other Solanaceous plant species, such as tomato, eggplant and pepper. To investigate the steroidal origin of SGA biosynthesis, cut potato shoots were fed cholesterol labelled with deuterium (D) in the sterol ring structure (D5- or D6-labelled), or side chain (D7-labelled), and analysed after three or five weeks. The labelled cholesterol and presence of D-labelled SGA were analysed by GC-MS an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 37 publications
1
8
0
2
Order By: Relevance
“…The biosynthetic pathways of cholestenol saponins, such as the important phytohormones sitosterol and brassinosteroids ( Symons and Reid, 2004 ), have been intensively studied ( Chu et al, 2005 ), while the biosynthesis of diosgenin, a spimstanol saponin, remains poorly understood. Previous work using isotope labeling has suggested that spimstanol saponins are derived from cholesterol ( Bennett and Heftmann, 1965 ; Tomita and Uomori, 1971 ), and reports have increasingly shown that cholesterol is the precursor of the C24-desmethyl sterols ( McCue et al, 2005 , 2006 , 2007 ; Itkin et al, 2011 , 2013 ; Petersson et al, 2013 ), providing further evidence to support the notion that dioscin is derived from cholesterol ( Figure 2 ). C24 methylation is the main divergence point between the biosynthesis of C24-desmethyl sterols and cholestenol saponins, and this process can be regulated by MeJA ( Ren et al, 2009 ).…”
Section: Resultssupporting
confidence: 52%
“…The biosynthetic pathways of cholestenol saponins, such as the important phytohormones sitosterol and brassinosteroids ( Symons and Reid, 2004 ), have been intensively studied ( Chu et al, 2005 ), while the biosynthesis of diosgenin, a spimstanol saponin, remains poorly understood. Previous work using isotope labeling has suggested that spimstanol saponins are derived from cholesterol ( Bennett and Heftmann, 1965 ; Tomita and Uomori, 1971 ), and reports have increasingly shown that cholesterol is the precursor of the C24-desmethyl sterols ( McCue et al, 2005 , 2006 , 2007 ; Itkin et al, 2011 , 2013 ; Petersson et al, 2013 ), providing further evidence to support the notion that dioscin is derived from cholesterol ( Figure 2 ). C24 methylation is the main divergence point between the biosynthesis of C24-desmethyl sterols and cholestenol saponins, and this process can be regulated by MeJA ( Ren et al, 2009 ).…”
Section: Resultssupporting
confidence: 52%
“…It seems plausible that the observed changes in the sterol pool are linked to a metabolic reaction against the infection by M. incognita . For example, in solanaceous plants, cholesterol can make up a significant portion of the overall sterol pool and has been suggested as a precursor of toxic steroidal alkaloids and glycoalkaloids [ 31 ]. Campesterol is used in numerous plants as precursor for the synthesis of brassinosteroid phytohormones, essential for the regulation of numerous plant processes, such as cell expansion and elongation, senescence and protection against drought and chilling [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…S3 . Sterols in experiments with transgenic plants were quantified by GC-MS using desmosterol, cycloeucalenol and 24-methylene cycloartanol as added internal standards for different sterol fractions 13 .…”
Section: Methodsmentioning
confidence: 99%
“…SGAs are derived from the isoprenoid pathway, and the sterol cholesterol has been identified as a metabolic precursor 11 12 13 ( Supplementary Fig. S1 ).…”
mentioning
confidence: 99%